"Rendez à César ce qui est à César, à Dieu ce qui est à Dieu": Méditation théologique sur Luc 20, 19-31 une année après les élections en R. D. Congo (Hekima Review, 2013)
Ever since Jesus Christ stood before Pilate, the representative of political authority, the relationship between the Church and the State has been an ongoing debate. As long as a Christian lives in this world, he will as a disciple of Christ, work strenuously to contribute towards the construction of a human society. The last elections in Africa, especially those held in D. R. Congo gave us an opportunity to re-open the debate regarding the relationship between the Church and the State. In fact during those elections, a phrase of the Gospel, “Then render to Caesar the things that are Caesar’s, and to God the things that are God’s.” (Luke 20:25) was especially used to exclude Christians from engaging in a debate about transparency during the elections and the credibility of the results that followed. Our article rejects this manipulative use of Scripture as an argument ad hominem, against the citizens of a country. We propose a contextual reading of this sentence of Jesus and an honest interpretation of it. This in turn will help us to better understand the healthy tension that ought to characterize the relationship between the Church and the state.